Improved minority carrier lifetime in p-type GaN by suppressing the non-radiative recombination process. (1st July 2022) - Yan, Shumeng; Liu, Jianxun; Zhou, Yu; Sun, Xiujian; Zhong, Yaozong; Chen, Xin; Tang, Yongjun; Guo, Xiaolu; Sun, Qian; Yang, Hui
Abstract: Time-resolved photoluminescence and capacitance-voltage measurement were performed on p-type GaN and InGaN films to study the minority carrier recombination mechanism. The minority carrier lifetime ( τ PL ) for p-GaN with a Mg concentration of 1.7 × 10 19 cm −3 was 46 ps. The non-radiative recombination due to gallium vacancies ( V Ga )-related defects is confirmed to dominate the minority carrier transport process. To suppress the formation of V Ga defects, the indium atoms were added into p-GaN. As a consequence, the V Ga -related non-radiative recombination centers were reduced from 8 × 10 15 to 5 × 10 14 cm −3 and a record long τ PL of 793 ps was obtained for p-In0.035 Ga0.95 N film.